Perspective correction of building facade images for architectural applications - Soycan, A.; Soycan, M. (ELSEVIER - DIVISION REED ELSEVIER INDIA PVT LTD, 2019)
In this study, a geometric method used to obtain rectified photographs that will form a base for drawings of building facades are examined. Mathematical model is presented by informing briefly about the method evaluated. The subject is exemplified by a test study. In the test study, firstly, the behavior of the related methods on the created artificial image was examined and the applications on the real photographic sets of the models obtained with different types and different cameras were performed. The obtained results were evaluated statistically and various conclusions were drawn and the suggestions were made for those who want to apply the method and want to do the study in this subject. (C) 2018 Karabuk University. Publishing services by Elsevier B.V.
Keywords: Photography; Architectural surveying; Photogrammetry; Image transformation; Rectification; Engineering